Faktor Risiko Terjadinya Kecelakaan pada Anak Sekolah dengan Retardasi Mental - Prajoga Rizky Camelia Bibi, Atik Choirul Hidajah (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Mental retardation is one of disabilities that can be implied in all families without any limitation of race, education and economic background. Mental retardation happened among Indonesia children is fairly high: in Surabaya, it predicted 1%-3%. Like any normally children, children with mental retardation have probability occurred in accidental, the probability could be greater because of cognitive limitation and its sensory and motorist development.Objective:The research is tried to find out risk factor of accidental occurred in mental retardation children.The risk factors will be beneficial as an effort to prevent and control.Methods: The research is done in irregular school C1 in Surabaya for 40 students with medium level of mental retardation (IQ between 30-55). Independent variables are children characteristics, row of birth, family protection, and time period of school. The dependent variable is accidental occurred in mental retardatioh. Data collection is done to respondents, which are parents of children. Descriptive analysis and measuring risk factors is implemented by calculating odds ratio (OR).Results: The research indicated that 40% children ever occurred in any accidental. Greater frequency of accidental is failing or slippery when running (50%). Falling or slippery from chair (18,75%); falling or slippery from bed (18,75%). Highest risk factor happened in the absence family protection (OR = 4,2) and did not happened on first children in row of birth (OR = 2,0).Conclusion: To prevent any accidental occurred, children with mental retardation should be frequency under control, either by special guardian or by family members. Construction of household or furniture must be adjusted in order to ease children in using them. The cleaning of bathroom and other places can prevent any accidental occurred in home. Due to the research is preliminary, it is suggested to do similar research in widen population and more complete variable such as adjustment of household utilities and high risk factors but not implies in population. Keywords: Mental retardation, accidents, risk factors